Haemolytic-Uraemic Syndrome as a Sequela of Diarrhoeal Disease - Walker, Christa L Fischer; Applegate, Jennifer A; Black, Robert E (Journal of Health, Population and Nutrition, 2012)
Haemolytic-uraemic syndrome (HUS) is a serious sequela of diarrhoea and results in a high mortality rate. This systematic review aimed at estimating the proportion of HUS cases that are linked to prior infection due to Shiga toxin-producing Escherichia coli (STEC) or Shigella dysenteriae type 1. A systematic review of the existing literature was done to identify cohort and case-control studies that examined the relationship between STEC and S. dysenteriae type 1 and HUS. After screening 2,516 articles, 11 studies were found that met the inclusion/exclusion criteria. Findings of case-control studies suggest that 60.8% of the HUS cases may be attributable to a previous infection with STEC. In cohort studies, 7.8% of participants with STEC and 8% of participants with S. dysenteriae type 1 developed HUS during follow-up. HUS is linked to diarrhoea due to both STEC and S. dysenteriae type 1. Thus, preventing infections caused by both pathogens is critical for the prevention and control of HUS, especially in areas where timely and effective treatment is not available. DOI: http://dx.doi.org/10.3329/jhpn.v30i3.12288 J HEALTH POPUL NUTR 2012 Sep;30(3):257-261